Accumulation, Timing, and Duration of Early Childhood Adversity and Behavior Problems at Age 9 - Schroeder, Allison; Slopen, Natalie; Mittal, Mona (Journal of clinical child and adolescent psychology, 2020)
We utilized a life course framework to examine associations between the accumulation, timing, and duration of adverse childhood experiences (ACEs) across early childhood (ages 1-5 years) and internalizing and externalizing behavior problems at age 9. The sample included 1,789 children from the Fragile Families and Child Wellbeing Study, a birth cohort study of children born between 1998 and 2000. Primary caregivers reported on seven ACEs at child ages 1, 3, 5, and 9. We created 2 summary measures of early childhood ACEs to capture (a) accumulation and (b) timing and duration. We derived indicators of caregiver-reported internalizing and externalizing problems at ages 5 and 9. Logistic regression was used to estimate associations between early childhood ACEs and behavior problems at age 9, sequentially adjusting for sociodemographic covariates, age 9 ACEs, and age 5 behavior problems. In fully adjusted models, children exposed to 6 or more ACEs in early childhood faced 3 times the odds of age 9 behavior problems, compared to children exposed to 0-1 ACE. Intermittent adversity was associated with the greatest increase in odds of age 9 behavior problems, relative to other early childhood timing/duration categories. Categories of high early and high late adversity were also associated with age 9 behavior problems. Chronic adversity was not associated with age 9 behaviors in final models that adjusted for age 5 problems. These results demonstrate the importance of a developmental perspective for understanding the role of childhood adversity in the etiology of child psychopathology.